(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the effectiveness of modular teaching technologies in fostering pluricultural competence among pre-service teachers. In today’s globalized educational context, future educators must not only possess linguistic skills but also demonstrate intercultural awareness and sensitivity. Pluricultural competence refers to the ability to understand, communicate, and interact across multiple cultures. The study presents a theoretical framework of pluricultural education and investigates the implementation of modular instruction as an innovative pedagogical approach in teacher education programs. Empirical data collected through questionnaires, reflective journals, and teaching simulations suggest that modular teaching enables structured, flexible, and culturally rich learning experiences.